Molecular Classification of Iraqi Breast Cancer Patients and Its Correlation with Patients’ Profile - Khudair J. Al-Rawaq; Manwar A. Al-Naqqash; Mustafa K. Jassim (مجلة كلية الطب, 2016)
Background: Breast cancer is a complex, multifaceted disease encompassing a great variety of entities that show considerable variation in clinical, morphological and molecular attributes. Objective: The aim of this study to evaluate patients’ molecular profile (Estrogen receptor, Progesterone receptor, HER2/neu and Ki-67). Patients & Methods: This is a cross-sectional descriptive study was done in Baghdad oncology teaching hospital from December 2015 to April 2016, carried on 100 breast cancer female patients with their age range from 27 to 73 years old and with their histopathology reports and (IHC) results. Results: The highest incidence of breast cancer among patients in 5th (40-49 years) and 6th (50-59 years) decades of life both groups are (32%), estrogen and progesterone values were observed (74% and 75% respectively) and 69 patients (69%) with Ki-67 ≥14. Conclusions: Most of the breast cancer patients in the current study were estrogen and progesterone (Hormonal) positive, and Luminal B-like was the most common molecular subtype (53%) due to high Ki-67 index. There was a strong correlation between estrogen and progesterone in the studied patients with highly significant P value <0.0001.